Vaccination in Chronic Obstructive Pulmonary Disease - Wang-Chun Kwok; Jin-Ning Clarabel Wong; Aaron Cheung; Terence Chi-Chun Tam (Vaccines)
Chronic obstructive pulmonary disease (COPD) is often exacerbated by various viruses and bacteria, leading to acute episodes of worsening respiratory symptoms, which contribute significantly to the morbidity and mortality associated with COPD. Consequently, vaccination against these pathogens is recommended by numerous guidelines to safeguard COPD patients from adverse health outcomes. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) recommendation advocates for vaccination against influenza, Streptococcus pneumoniae, respiratory syncytial virus (RSV), severe acute respiratory syndrome coronavirus (SARS-CoV2), pertussis, and varicella zoster. This review article will examine the current vaccination strategies recommended for adult COPD patients and will discuss the clinical benefits associated with these vaccines.